A Comprehensive Assessment of HVAC Preventive Maintenance Effectiveness in Controlling Indoor Air Quality in Hospital Buildings - Muhamad Shahril Mohd Abdullah; Mohd Arif Rosli; Mohd Syafiq Syazwan Mustafa; Azian Hariri; Amir Abdullah Muhamad Damanhuri (International Journal of Sustainable Construction Engineering and Technology, 2025)
Indoor Air Quality (IAQIndoor Air Quality (IAQ) is critical in hospital environments due to the increased vulnerability of patients and healthcare workers to airborne contaminants. Maintaining optimal IAQ is essential for protecting health and ensuring a safe clinical environment. This study evaluates the effectiveness of HVAC Planned Preventive Maintenance (PPM) in improving IAQ within hospital wards, following guidelines from the Department of Occupational Safety and Health (DOSH) and the Ministry of Health (MOH) under ICOP 2010. A case study approach was applied in two hospital wards with centralized HVAC systems. IAQ measurements were taken before and after PPM interventions. Ethical approval was obtained, and monitoring was conducted in collaboration with hospital management and the National Institute for Occupational Safety and Health (NIOSH) Malaysia. The Wilcoxon signed-rank test revealed significant improvements (p < 0.05) in case study 1 for temperature, air movement, TVOC, CO₂, CO, CH₂O, O₃, and PM2.5. In case study 2, significant changes were noted for RH, PM10, CO₂, O₃, and PM2.5. However, parameters such as microbial counts, PM10 (CS1), and temperature (CS2) showed no significant change. These findings highlight the positive impact of PPM on IAQ while identifying areas that require targeted improvements, supporting the development of more effective HVAC maintenance strategies in healthcare settings.